Studi Analisa Pengaruh Pembebanan Dan Temperatur Lingkungan Terhadap Susut Umur Tranformator Daya Pada Gardu Induk Garuda Sakti - Kurniawan, Kurniawan; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Power transformers is an essential equipment in the distribution of electricity to a substation, thus cultivated a power transformer to function in accordance with its design lifespan. The loss of life power transformers is affected by several important parameters. The Parameters is end of the hot spot temperature, loading operations and environment temperature. The method is gathering the data, data proccessing, and analysis. The results of the study showed a third hotspot temperature transformer in Garuda Sakti substations still within safe limits set by International Electrotechnical Commission (IEC) standard. Loading has a considerable effect on the final value of the hotspot temperature than the ambient temperature. Loss of life transformers in Garuda Sakti substations each totaled 0.00017 % of transformer 1, 0.0004 % of transformers 2 and 0.00023 % of transformer 4.Keyword : power transformer, hot spot temperature, loss of life